Tourism experiences of persons with disabilities in Malaysia: voices of mobility-impaired people - Saad, Mazni; Muhammad Goh Kee Leok, Ameen Noor Aqilah; Ahmad, Siti Yuliandi; Abukhalifeh, Alaa Nimer (e-International Publishing House, Ltd., UK., 2025)
Tourism is a fundamental right, yet mobility-impaired Persons with Disabilities (PwDs) face significant barriers in Malaysia. This study explores their tourism experiences, highlighting challenges such as inadequate infrastructure, limited independence, and insufficient support from tourism providers. Using a qualitative phenomenological approach, four semi-structured online interviews were conducted. Findings reveal a need for accessible transport, accommodations, and inclusive event planning. Advocating for universal design principles and comprehensive accessibility guidelines, this study emphasizes the urgency of inclusive policies to ensure PwDs can travel with dignity, independence, and confidence, fostering a more equitable tourism landscape.